TECHNOLOGICAL ONSLAUGHT AND THE DEMISE OF A DEDICATED MANUFACTURING PLANT - Ghazali, Zulkipli; Halib, Mohammed (World Business Institute, Australia, 2005)
The phenomenal growth of the wireless information and communications technology (ICT) has brought about unprecedented impact on the economy and society. This paper discusses the winding up of a manufacturing plant that produces concrete poles that are used to support traditional telecommunication overhead copper cables. The emergence of downstream substitutes by fiber optics and wireless telecommunication technologies has placed great pressure to the sales of the concrete poles. The company is rapidly declining and fighting a losing battle due to the sheer drop in the demand for the concrete poles caused by the substitutes and the stiff and volatile competition within the concrete industry. The rigidity of the manufacturing technology and state-of-art equipment that increased the hurdle for product diversification within the existing facility of the plant further compounded the problem.